Pendekatan Praktis Guru dalam Menganalisis Multiple Intelligence Anak Usia Dini di Kelas B4 RA Takhrimah Tungkop - Asyifa Turrahmi; Radhiyatul Muna; Yerina Elma Astari. HM; Silvia Fahmi Ramadani; Riza Lailiza; Ayu Mustira (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This research examines the practices of a B4 class teacher at RA Takhrimah Tungkop in identifying children’s Multiple Intelligences (MI) through authentic observation during an activity of printing moon shapes using banana stems. The study employed a descriptive qualitative approach with data collected through in-depth interviews and participatory observation. Data were analyzed thematically and supported by source and technique triangulation to ensure the validity of the findings. The results indicate that the teacher’s understanding of the MI concept was still focused on linguistic, logical-mathematical, and visual-spatial intelligences. Despite this limited conceptual scope, the implementation of authentic observation during the art-based activity successfully revealed a broader range of children’s intelligences. The moon-printing activity demonstrated indicators of visual-spatial intelligence through shape recognition and composition, bodily-kinesthetic intelligence through hand–eye coordination and motor control, and intrapersonal intelligence reflected in children’s ability to manage emotions, maintain focus, and show persistence during the task. Repeated observations accompanied by anecdotal records enabled the teacher to construct individual and continuous MI profiles for each child. These profiles can be utilized to design more varied, contextual, and child-centered learning strategies that align with the characteristics of early childhood learners in the Raudhatul Athfal setting. The practices observed also illustrate the connection between Gardner’s MI theory and Islamic early childhood education grounded in concrete learning activities. The findings support the development of child-friendly learning environments and encourage teacher creativity in conducting activity-based assessments. This study recommends strengthening teacher competencies through training in authentic MI assessment and further research using a research and development approach.